"The Waste Land" by Thomas Stearns Eliot and the Problem of Historicity of Subject - Wiśniewski, Tomasz (Sensus Historiae, 2025)
The aim of this paper is to outline a possible interpretation of Thomas Stearns Eliot’s poem The Waste Land in the context of the problem of the historicity of subject, drawing on certain concepts from Martin Heidegger’s Being and Time. Eliot’s poetry, which is largely concerned with time, its figurations and possible relationships with it, provides an excellent field for such an experiment. In contrast to categories describing other types of being, it is existentials - that is, the characteristics of being such as Dasein (being there) - that prove to be a key factor. Existentials likely include temporality and historicity, from which the thematized concepts of time and history are derived. This interpretation does not decide whether the Dasein of The Waste Land - whatever it may be, as there are various possible ways to denote it - possesses temporality or historicity. Instead, through engagement with the text, the possibility emerges of outlining another existential, namely elementality, the phenomenal aspect of which would be the elements of nature, recurring repeatedly in the poem. This suggests the existence, somewhat alongside temporality and historicity, of a distinct realm whose identification and conceptualization could have a revitalizing impact on contemporary historical thinking.